The morphology and taxonomy of invasive weeds from various habitats in the Ashanti Region, Ghana - Anning, Alexander Kofi (2011)
A thesis submitted to the Department of Theoretical and Applied Biology, College of Science in partial fulfilment of the requirements for the degree of Master of Science, 2004